1981
DOI: 10.1111/j.1476-5381.1981.tb08735.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antimuscarinic Agents on the Contractile Responses to Cholinomimetics in the Rat Anococcygeus Muscle

Abstract: The effects of antimuscarinic agents alone and in the presence of neostigmine on the contractile responses to exogenously applied cholinomimetics or (‐)‐noradrenaline were studied in the rat anococcygeus muscle. Atropine (1 × 10_9‐1 × 10−6m) alone, in the presence of hexamethonium (1 × 10−4m), or phentolamine (1 × 10−6m), inhibited responses to acetylcholine but not to (—)‐noradrenaline. The inhibitory effect with the higher concentrations of atropine (1 × 10−8— × 10−6m), was seen as an increase in the slopes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…The Kbe value of atropine was 0.54 nmol 1- (Table 2), a value already reported in this tissue (Doggrell, 1981). The 4 values Kbe values 100 nmol 1-'/(DRe-1) are given in Table 1.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…The Kbe value of atropine was 0.54 nmol 1- (Table 2), a value already reported in this tissue (Doggrell, 1981). The 4 values Kbe values 100 nmol 1-'/(DRe-1) are given in Table 1.…”
Section: Resultssupporting
confidence: 62%
“…In the (0-2.5 h) period, the Kbe value of AR-C239 was 0.80 nmol 1-l (Table 2), which shows that this drug is much more potent than thymoxamine (Kbe=30nmolI-, Table 1). The Kbe value of atropine was 0.54 nmol 1- (Table 2), a value already reported in this tissue (Doggrell, 1981). The 4 values Kbe values 100 nmol 1-'/(DRe-1) are given in Table 1.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Doggrell (1981) has shown that neostigmine (10-6M) did not alter contractile responses to (-)-noradrenaline itself.…”
Section: Choline Acetyltransferasementioning
confidence: 97%